A study of undergraduate ELT students' motivation in Libya - Alkorbow, Abdalmonam Hassan Saleh; Eldeeb, Wegdan Saad (Brilliance: Research of Artificial Intelligence, 2021)
Learning languages requires desire and practices from the learners; one of the major things that guide better learning is motivation in learning process to be more skilful. Thus, this study attempts to describe and examine students’ motivation of ELT undergraduate students in Tripoli University in Libya. The main purpose of this study is to examine students' intrinsic and extrinsic motivation toward learning English as a foreign language in Libya.The study tries to find out those factors that may affect the students' motivation negatively. In the study, 150 ELT Libyan undergraduate students (121 males & 29 females) participated fill the questionnaire to figure out the students’ tendency throughout the extrinsic motivation to investigate what affects their English learning process and how to motivate undergraduate students from the ages between 17 to 25 years in various levels range from 1st to 4th year. Unpredictably, the data discovered that the students have a higher degree of extrinsic rather than intrinsic motivation. The results were not expectable; the study's findings were unusual as Libyan students' integrative orientation was higher than their instrumental motivation.